Polyvinylidene Fluoride‐Based Vibration Energy Harvester with Piezoelectric and Electromagnetic Effects. Issue 12 (20th October 2022) - Ao, Hongrui; Meng, Yuxin; Li, Yihao; Li, Rongqi; Jiang, Hongyuan
Abstract : Vibration energy harvesting technology aims to convert mechanical energy into electrical energy through piezoelectric effect or electromagnetic induction to supply energy for wireless sensors. Herein, based on polyvinylidene fluoride, a vibration energy harvester who couples piezoelectric effect and electromagnetic induction is proposed, and its performance of energy harvesting is studied from the aspects of multiphysical field, microscale, and energy harvesting circuit. First, a mass‐spring‐damper model is established from the dynamic point of view, and the equivalent circuit models of piezoelectric unit and electromagnetic unit are established from the electrical point of view. Second, the effects of the nonlinear magnetic field, temperature, and microvolume on the resonant frequency and output power density of the energy collector are analyzed by simulation. Finally, a piezoelectric electromagnetic composite energy harvesting circuit is designed and the output voltage rectifying and stabilizing with high electromechanical conversion efficiency is realized. The results show that the harvester realizes the expected functions of inputting alternating current and outputting direct current, with open circuit output voltage up to 6.55 V and output power up to 2.21 mW. This study provides a valuable reference for the research in the field of vibration energy harvesting. Abstract : A vibration energy collector consisting of an electromagnetic unit and a piezoelectric unit is designed. The device can be connected to other external devices through the specific circuit. This structure can take the advantages of both energy harvesting methods and obtain better output voltage and power. Herein, the influence factor of the output performance is studied experimentally.